Streptococcus suis Research: Progress and Challenges - Mariela Segura (Pathogens, 2020)
Streptococcus suis is considered among the top bacterial pathogens leading to important economic losses to the swine industry, with the incidence of disease increasing as the prophylactic use of antimicrobial is being vanished worldwide. S. suis is also a zoonotic agent afflicting people in close contact with infected pigs or pork meat. Besides, in some Asian countries, it is considered a major public health concern for the general population as well. Antimicrobial resistance is one of the most important global health challenges, and in the absence of preventive measures (such as effective vaccines), S. suis remains a risk for increased antimicrobial resistance and transmission of resistance genes to other bacteria beyond the host animal species. The studies in this Special Issue have evidenced the importance of swine population demographics and management on disease control, progress in molecular tools to better understand the epidemiology of S. suis infections in swine and humans, and the mechanisms involved in different aspects of the immuno-pathogenesis of the disease. The importance of reducing the prophylactic use of antimicrobials in livestock productions and the development of alternative control measures, including vaccination, are herein discussed.